2000
DOI: 10.1002/(sici)1522-2594(200001)43:1<111::aid-mrm13>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of shear waves generated by focused ultrasound

Abstract: This study has shown that magnetic resonance elastography (MRE) can detect shear waves excited by focused ultrasound (FUS) in both gel phantoms and ex vivo muscle. Good agreement was shown between the shear modulus measured from MRE images generated using FUS and that using previously reported MRE techniques. The shear wave displacement amplitude at the FUS focus was studied and found to be proportional with both FUS ultrasonic pulse intensity and the FUS modulation pulse period over the range tested. Magn Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 11 publications
3
55
0
Order By: Relevance
“…It also showed that the estimated displacements were proportional to the applied acoustic power as expected for linear, plane-wave ultrasound propagation 16,40 and that in some situations the transverse component of the displacement can be mapped. This technique has potential uses for elastography and for guiding and monitoring therapies based on pulsed ultrasound exposures, such as targeted drug delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also showed that the estimated displacements were proportional to the applied acoustic power as expected for linear, plane-wave ultrasound propagation 16,40 and that in some situations the transverse component of the displacement can be mapped. This technique has potential uses for elastography and for guiding and monitoring therapies based on pulsed ultrasound exposures, such as targeted drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…17 This work is not the first to use focused ultrasound as a source for MRI-based elastography. In addition to the studies discussed above, 16,17,27 Sinkus et al recently presented preliminary data using an approach similar in many ways to MR-ARFI to guide high-power focused ultrasound thermal ablation. 47 Also, in one of the first tests of MRI-based elastography, Sarvazyan et al used focused ultrasound as a local source for shear waves, which were detected using a line scan sequence similar to that used in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 An alternative way of generating tissue motion is by using acoustical radiation force ͑ARF͒ from focused ultrasound ͑FUS͒. [8][9][10][11][12][13][14][15][16] One advantage of this approach is potentially higher displacement amplitude at deep tissues. Furthermore, the motion is localized near the focus, therefore avoiding the complicated issues of wave reflection by bones or other structures commonly associated with surface drivers.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,8] We refer to these techniques in general as Shear Wave Elasticity Imaging (SWEI). In linear, isotropic, elastic media, the shear wave propagation speed, SWS is directly related to the material's stiffness quantified by the Young's modulus E. We and others [9,10,11,12,13] have demonstrated that, although the complexity of cervical microstructure forbids the derivation of E from SWS estimates, the latter can be feasibly used to track changes in cervical stiffness in humans.…”
Section: Introductionmentioning
confidence: 99%